(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The main structural and functional element of the kidneys is the nephron, which consists of a glomerulus (branching of renal capillaries) located inside the double-walled Shumliansky-Bowman capsule (capsula glomeruli), which extends into a system of renal tubules flowing into the urinary tubes. Nephrons are divided into superficial (surface), intracortical and juxtamedullary.